Undifferentiated embryonal sarcoma and the role of liver transplantation - Leah Plumblee; Helen Grey; Michelle Hudspeth; Satish Nadig (Elsevier, 2019)
Undifferentiated embryonal sarcoma of the liver (UESL) is a rare but aggressive pediatric tumor. Historically, treatment for UESL has consisted of combination therapy with surgical resection and chemotherapy. In some cases, surgical resection is not appropriate due to limiting factors such as tumor size, location, and lack of response to treatment. Orthotopic liver transplant (OLT) has been suggested as a promising alternative in these cases. We present a case of an 8 year-old boy with a large undifferentiated embryonal sarcoma of the liver who experienced disease progression after initial neoadjuvant chemotherapy. His tumor was considered unresectable after internal tumor board review due to its size and significant vascularity, ultimately making OLT the only curative option for this patient. Keywords: Undifferentiated embryonal sarcoma of the liver, Pediatric liver tumors, Orthotopic liver transplant, Pediatric liver transplantation